Epidemiology and Outcomes of Hematopoietic Stem Cell Transplantation in Human Immunodeficiency Virus-Positive Patients From 1998 to 2012: A Nationwide Analysis. (6th January 2018) - Mehta, Kathan; Im, Annie; Rahman, Farah; Wang, Hong; Veldkamp, Peter
Abstract : Frequency of Hematopoietic Stem Cell Transplantation (HSCT) is increasing in HIV-positive patients. Serious in-hospital complications of HSCT are similar in HIV-positive and HIV-negative patients after allogeneic and autologous HSCT. Allogeneic and autologous HSCT can be safely performed in HIV-positive patients. Abstract: Background: Prior studies have shown that outcomes of hematopoietic stem cell transplantation (HSCT) in human immunodeficiency virus (HIV)–positive patients have been similar to outcomes in HIV-negative patients since effective implementation of highly active antiretroviral therapy by 1998, but they are limited by small sample size or noninclusion of recent data. Methods: We queried National Inpatient Sample, a large inpatient data set in the United States, from 1998 to 2012 for HSCT, using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) procedure code 41.0. HIV-positive patients were identified by the presence of ICD-9-CM diagnostic codes 042, 043, 044, V08, and 079.53. The primary outcome was in-hospital mortality rate, and the secondary outcome the in-hospital complication rate of HSCT. Outcomes were assessed by means of univariate, multivariate regression and matched-pair analysis. Results: A total of 39517 patients who underwent HSCT were identified. Among these, 108 patients had HIV infection. There were no differences in in-hospital mortality rates or rates of intubation, sepsis, bacteremia, or graft-vs-host disease between HIV-positive and HIV-negative patients after allogeneic or autologous HSCT. In allogeneic HSCT, HIV-positive patients had a significantly higher incidence of nontuberculous mycobacterial and cytomegalovirus infection than HIV-negative patients. Conclusion: Although HIV-positive patients may have a higher risk of certain opportunistic infections, they are not at higher risk of serious in-hospital complications of HSCT. Allogeneic and autologous HSCT can be safely performed in HIV-positive patients.